Precious metals trading : - Gotthelf, Philip (John Wiley & Sons, 2005)
A detailed look at how to profit in the precious metals market Today, gold, silver, platinum, and palladium offer a new and different profit potential for those who understand the impact of new technologies, new economic forces, and new demographics. Updated to reflect changes in this market since the mid-1990s, The Precious Metals Trader focuses on new developments that could translate into serious profit-making trends-from electrically-generated automobiles that could substantially increase demand for platinum to the increased use of composites in dentistry, which could negatively impact the use of both silver and gold. The Precious Metals Trader also explains the supply/demand fundamentals of the four precious metals-gold, silver, platinum, and palladium-and provides projections about long-term trends and profit opportunities that will coincide with them. Filled with fresh insights from Philip Gotthelf-one of the top experts in this field-The Precious Metals Trader offers readers the guidance they need to trade profitably within this dynamic market. Philip Gotthelf (Closter, NJ) publishes the Commodex System-the oldest daily futures trading system published in the world-and the Commodity Futures Forecast Service. He is also President of Equidex Incorporated and Equidex Brokerage Group Inc.